The meaningfulness of "The Meaninglessness of Ritual": [an advaita Vedānta perspective on] Vedic ritual (yajña) as narrative of renunciation (tyāga) - Loundo, Dilip (Horizonte, 2018)
The objective of the present article is to suggest that systematic, deliberate and gradual renunciation (tyāga) constitutes the fundamental thrust of Indian Vedic traditions and the main feature of what may be called a religious or spiritual outlook, in contrast with a mundane one. I'll try show that renunciation is ultimately purportful in enabling one to overcome suffering (duḥkha) through gradual immersion into the knowledge of the deepest levels of one's immediate Reality. Considering the two-step ladder that make-up Vedic religious designs according to Advaita Vedānta - viz., karma as ritual-related actions leading to improved rebirths, and jñāna as knowledge-related disciplines leading to ultimate self-realization, - the specific focus of the present article will be on the first step. Accordingly, I'll strive to unveil the specific characteristics, modalities and cognitive facets of renunciation that make up, in my opinion, the fundamental meaning of dharma as a goal to be pursued in accordance with the narrative prescriptions of the Vedas and in the form of ritual actions - karma -, leading one to paradise in next life.